Development and Evaluation of an Interactive AI-Powered Robotic Assistant for Language Learning - Torres-Caballero, Salvador Joaquín; Paz-Ortega, Esteban Joaquín; Castro-Vargas, Cristian (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Accessibility and quality of educational resources remain significant challenges, particularly in resource-limited contexts. This study presents an AI-powered interactive robotic assistant designed to enhance language learning. The assistant integrates vocal, visual, and gestural interactions using a Raspberry Pi, Arduino, a TFT display, servo motors for motion, and a natural language processing system. In addition, the system incorporates mobile-based interaction for remote control and progress monitoring. The assistant dynamically adjusts content to student needs using educational personalization algorithms and provides automated assessments to adapt to the difficulty of activities. The solution is designed with low-cost hardware, such as cardboard enclosures and basic peripherals, and prioritizes sustainability and scalability. Preliminary results indicate improved student engagement and motivation by combining auditory, visual, and kinesthetic elements. The study concludes that the robotic assistant has significant potential to transform language learning through an accessible, mobile-enhanced interactive solution.